L’enfant des villes. Considérations sur la place du jeu et la créativité de l’architecte face à l’émergence de la ville garantie - Marc Breviglieri (Ambiances)
The presence of young children in the street sometimes manifests itself through moves to escape or explore beyond parental supervision. Taking a closer look, the inspired manifestation of such gestures of escape reveals an essential dimension of the sensory relation to the urban environment, which architects should bear in mind. A child can make the city exist differently, revealing a particular texture which an adult often no longer registers. But this opening into the child’s phenomenal field, which may help architects in their efforts of imagination, is subject to a contrary tension due to an array of normative technical directives and constraints entailed by the spread of quality-certification policies, particularly forcible with regard to children and urban design. In their drive to guarantee reasonable, informed use of the city, such policies eliminate many of the loopholes through which play may break out into the public space, thus depriving children of the opportunity to learn to live with others, potentialize remarkable abilities and, perhaps, discover a place of unique delight.